PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, DAN THIN CAPITALIZATION TERHADAP TAX AVOIDANCE - Fathurrahman, Ikhsan; Andriyanto, W.A.; Dyah Pita Sari, R.H (Universitas Djuanda, 2021)
This study aims to determine the effect of institutional ownership, audit committee, and thin capitalization on tax avoidance in 137 manufacturing sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research is a type of quantitative research using secondary data in the form of the company's annual report. The Random Effect Model (REM) with panel data regression was used in this study using STATA version 16. Based on the test results and analysis, it can be concluded that thin capitalization have a significant negative effect on tax avoidance, while institutional ownership and audit committee has no effect on tax avoidance.